2017
DOI: 10.6061/clinics/2017(01)08
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Vertebral Fracture in Patients Diagnosed with a Depressive Disorder: A Nationwide Population-Based Cohort Study

Abstract: OBJECTIVE:Previous studies have reported that depression may play a crucial role in the occurrence of vertebral fractures. However, a clear correlation between depressive disorders and osteoporotic fractures has not been established. We explored the association between depressive disorders and subsequent new-onset vertebral fractures. Additionally, we aimed to identify the potential risk factors for vertebral fracture in patients with a depressive disorder.METHODS:We studied patients listed in the Taiwan Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 49 publications
0
17
0
1
Order By: Relevance
“…Of the 16 studies, most were from America (eight studies) or European countries (five studies). Meanwhile, one study was conducted in Australia [ 20 ] and two in Taiwan [ 8 , 21 ]. Nine studies comprised both men and women, with four reporting results that were based on sex group, two studies included men only [ 22 , 23 ], and five studies involved only women [ 20 , 24 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 16 studies, most were from America (eight studies) or European countries (five studies). Meanwhile, one study was conducted in Australia [ 20 ] and two in Taiwan [ 8 , 21 ]. Nine studies comprised both men and women, with four reporting results that were based on sex group, two studies included men only [ 22 , 23 ], and five studies involved only women [ 20 , 24 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies comprised both men and women, with four reporting results that were based on sex group, two studies included men only [ 22 , 23 ], and five studies involved only women [ 20 , 24 27 ]. In most of the studies, depression was assessed using self-reported symptom scales, and in three studies, the condition was confirmed based on the physician’s diagnosis [ 8 , 21 , 28 ]. With regard to fracture types, only five studies reported about any fracture [ 7 , 20 , 23 , 26 , 29 ], and only four studies were about hip fracture [ 8 , 9 , 27 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced bone mass, especially osteoporosis, is significantly more common in people with schizophrenia, bipolar disorder, and depression than controls [9][10][11] . Genetic framework and the use of psychotropic medications play a major role in the preeminent risk of physical morbidity and mortality related to these disorders, including metabolic disorders, endocrine diseases, and fractures.…”
Section: Genetic Susceptibilitymentioning
confidence: 99%
“…Die Assoziation zwischen Depression und Fraktur wurde nicht nur für Hüftfrakturen, sondern z. B. auch für vertebrale Frakturen beschrieben [6,7].…”
Section: Introductionunclassified